2022
DOI: 10.1007/s10895-022-03042-w
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Excited-state Double Proton Transfer and Fluorescence Decay Analysis

Abstract: This work considers excited state intramolecular proton transfers (ESIPT) occurred in multiple hydroxyl-containing compounds with one proton transfer site in the normal form. If several hydroxyl groups are located close to each other in a molecule, then the ESIPT process can lead to the next one. A proton donor site in the first ESIPT will be a proton acceptor during the second reaction. Therefore, a number of consecutive excited state proton transfers can occur. This work deals with the case of two successive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Kinetic analysis of the results for reactions (3) and (4) showed satisfactory agreement with experimental data and the rate constants of these reactions 2•1010 and 8•109 l 2 /mol 2 s, respectively, were obtained [21]. At present, the absorption spectroscopy method based on the phenomenon of selective absorption of radiation by gases is widely used [23; 24].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Kinetic analysis of the results for reactions (3) and (4) showed satisfactory agreement with experimental data and the rate constants of these reactions 2•1010 and 8•109 l 2 /mol 2 s, respectively, were obtained [21]. At present, the absorption spectroscopy method based on the phenomenon of selective absorption of radiation by gases is widely used [23; 24].…”
Section: Introductionsupporting
confidence: 56%
“…Since sodium atoms have low electronic levels, only a portion of the recombination heat released by the reaction is sufficient to excite them, and the presence of low-lying ionic terms increases the probability of energy transfer between them. Several are known to explain the coloring of hydrogen-burning flames by the addition of sodium atoms and the addition of sodium to the stream of hydrogen atoms coming out of the electric discharge tube [20][21][22]. Two elementary acts leading to the manifestation of excited sodium atoms are considered:…”
Section: Introductionmentioning
confidence: 99%
“…Excited-state double proton transfer (ESDPT) constitutes an even more interesting phenomenon because two protons can be translocated within the same molecular structure, either by a synchronous or asynchronous mechanism. 38–47 As an example, a simple compound such as [2,2′-bipyridyl]-3,3′-diol shows photoexcited double proton transfer with emission bands at 510 and 568 nm related to the diketo and monoketo forms. 39,48 Experimental and theoretical studies indicated that the most likely mechanism is a sequential proton transfer.…”
Section: Introductionmentioning
confidence: 99%